Technika obrazowaniaCoexistence of coarctation of aorta and anomalies of aortic arch arteries on the basis of vascular examinations in 64-slice computed tomography - Głowacki, Jan; Maślanka, Patrycja; Miszalski-Jamka, Karol; Szkutnik, Małgorzata; Wasilewski, Jarosław; Jarski, Piotr; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Aortic coarctation is an aortic stenosis at the level of the isthmus, next to the ductus arteriosus or attachment of the ligament arteriosus, below the beginning of the left subclavian artery. This defect occurs as an isolated stenosis or associated with other failures. Aim: The aim of the study was to compare the occurrence frequency of aortic coarctation and anomalies of aortic arch arteries. Material and Methods: Retrospective analysis included 53 patients with diagnosed coarctation of aorta with 64-slice CT in the Silesian Centre of Heart Diseases in the last 13 months. Results: The structure of aortic arch arteries was typical in 37 cases, brachio-cephalic trunk, left common carotid artery and left subclavian artery. Anomalies of aortic arch arteries were observed in 15 cases (28.85%). Conclusions: Multislice computed tomography proved to be very useful in the evaluation of coarctation and coexisting anatomic structures. A diagnostic examination can significantly influence the choice of treatment type (angioplasty, stenting, surgery); the analyses of CT examinations can indicate an increased frequency of the coexistence of aortic coarctation and anomalies of aortic arch arteries in comparison to normal aorta.